2019
DOI: 10.5194/os-15-967-2019
|View full text |Cite
|
Sign up to set email alerts
|

Skill assessment of global, regional, and coastal circulation forecast models: evaluating the benefits of dynamical downscaling in IBI (Iberia–Biscay–Ireland) surface waters

Abstract: Abstract. In this work, a multi-parameter inter-comparison of diverse ocean forecast models was conducted at the sea surface ranging from global to local scales in a two-phase stepwise strategy. Firstly, a comparison of CMEMS GLOBAL and the nested CMEMS IBI regional system was performed against satellite-derived and in situ observations. Results highlighted the overall benefits of both the GLOBAL direct data assimilation in open water and the increased horizontal resolution of IBI in coastal areas. Besides, IB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 80 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…This is particularly true in the NW Iberian waters, where coastal meanders and migratory eddies have been documented to exist and have ecological implications as nutrient conveyors [70,71]. In this context, previous studies demonstrated that small-scale coastal processes are poorly reproduced (or even misrepresented) in coarser grid meshes, suggesting the strong necessity of finer horizontal resolution in both hydrodynamic models [72] and HFR systems [46] to properly capture such littoral phenomena. Since this topic remains open and disputable, further investigations should be conducted to shed light on it.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true in the NW Iberian waters, where coastal meanders and migratory eddies have been documented to exist and have ecological implications as nutrient conveyors [70,71]. In this context, previous studies demonstrated that small-scale coastal processes are poorly reproduced (or even misrepresented) in coarser grid meshes, suggesting the strong necessity of finer horizontal resolution in both hydrodynamic models [72] and HFR systems [46] to properly capture such littoral phenomena. Since this topic remains open and disputable, further investigations should be conducted to shed light on it.…”
Section: Discussionmentioning
confidence: 99%
“…The model includes the atmospheric dust deposition of Fe, Si, P and N at the ocean surface (Aumont et al, 2015). River discharge of nutrients comes from the Global NEWS 2 datasets (Mayorga et al, 2010) and carbon comes from Ludwig et al (1996). An iron source corresponding to sediment reductive mobilisation on continental margins is also considered.…”
Section: Model Initialisation External Forcing and Boundary Conditionsmentioning
confidence: 99%
“…These regional coupled systems, and of course the 1/4 • NEMO-PISCES global ocean operational system, are the subject of intercomparisons. Ocean dynamics forecast models, all of them based on NEMO, are already being compared in Lorente et al (2019) and Mason et al (2019). For the marine biogeochemistry and ecosystem dynamics, intercomparison is initiated in the framework of CMEMS but represents a significant work because the biogeochemical models differ in complexity .…”
Section: Introductionmentioning
confidence: 99%
“…Combining enhanced high-frequency ocean observations, such as high-frequency (HF) radar currents, and different operational model products, Lin et al (2016) assessed an operational system at the Taiwan strait whose bias compared with HF-radar was close to -0.07 m/s under a calm regime; but double it (around 0.15 m/s) during typhoons Sinlaku (2008) and Morakot (2009). Likewise, Lorente et al (2019b), takes advantage of a long-term coverage of HF-Radar surface currents in the Gibraltar Strait area to provide a deeper analysis on the surface Atlantic jet variability. This work demonstrated the steady model improvement, when moving from global to coastal scales through a multi-nesting approach.…”
Section: Introductionmentioning
confidence: 99%